Validation of the Phase II Feasibility Study in a Palliative Care Setting: Gastrografin in Malignant Bowel Obstruction. (December 2013) - Lee, Cindy; Vather, Ryash; O'Callaghan, Anne; Robinson, Jackie; McLeod, Briar; Findlay, Michael; Bissett, Ian
Background: Malignant bowel obstruction (MBO) is common in patients with advanced cancer. Aim: To perform a phase II study to assess the feasibility of conducting a phase III trial investigating the therapeutic value of gastrografin in MBO. Methods: Randomized double-blinded placebo-controlled feasibility study. Participants received 100 mL of either gastrografin or placebo. Results: Over 8 months, 57 patients were screened and 9 enrolled (15.8% recruitment rate). Of the 9 enrolled, 4 received gastrografin (with 2 completing assessment) and 5 received placebo (with 4 completing assessment). Conclusions: It is not feasible to conduct a phase III trial using the same study protocol. This study validates the use of the phase II feasibility study to assess protocol viability in a palliative population prior to embarking on a larger trial.